Effectiveness of a Step Counter Smartband and Midwife Counseling Intervention on Gestational Weight Gain and Physical Activity in Pregnant Women With Obesity (Pas and Pes Study): Randomized Controlled Trial - Elena Gonzalez-Plaza; Jordi Bellart; Ángela Arranz; Leila Luján-Barroso; Esther Crespo Mirasol; Gloria Seguranyes (JMIR Publications, 2022)
BackgroundWomen who are pregnant and have obesity and excessive gestational weight gain (GWG) present a higher risk of maternal and perinatal complications. The use of mobile apps and a wristband during pregnancy may contribute to promoting healthy lifestyles and, thus, improving maternal and neonatal health. ObjectiveThis study aims to evaluate the effectiveness of a complex digital health intervention, using a smartband and app with midwife counseling, on GWG and physical activity (PA) in women who are pregnant and have obesity and analyze its impact on maternal and perinatal outcomes. In addition, we aim to study the frequency of use, usability, and satisfaction with the mobile apps used by the women in the intervention group. MethodsA parallel, 2-arm, randomized controlled trial was conducted. A total of 150 women who were pregnant and had obesity were included. The intervention group received a complex combined digital intervention. The intervention was delivered with a smartband (Mi Band 2) linked to the app Mi Fit to measure PA and the Hangouts app with the midwife to provide personal health information. The control group received usual care. The validated Spanish versions of the International Physical Activity Questionnaire-Short Form and the System Usability Scale were used. Satisfaction was measured on a 1- to 5-point Likert scale. ResultsWe analyzed 120 women, of whom 30 (25%) were withdrawn because of the COVID-19 pandemic. The median GWG in the intervention group was 7.0 (IQR 4-11) kg versus 9.3 (IQR 5.9-13.3) kg in the control group (P=.04). The adjusted mean GWG per week was 0.5 (95% CI 0.4-0.6) kg per week in the control group and 0.3 (95% CI 0.3-0.4) kg per week in the intervention group (df=0.1, 95% CI −0.2 to 0.03; P=.008). During the 35 and 37 gestational weeks, women in the intervention group had higher mean PA than women in the control group (1980 metabolic equivalents of tasks-minutes per week vs 1386 metabolic equivalents of tasks-minutes per week, respectively; P=.01). No differences were observed between the study groups in the incidence of maternal and perinatal outcomes. In the intervention group, 61% (36/59) of the women who were pregnant used the smartband daily, and 75% (44/59) evaluated the usability of the Mi Fit app as excellent. All women in the intervention group used the Hangouts app at least once a week. The mean of the satisfaction scale with the health counseling app and midwife support was 4.8/5 (SD 0.6) points. ConclusionsThe use of a complex mobile health intervention was associated with adequate GWG, which was lower in the intervention group than in the control group. In addition, we observed that the intervention group had increases in PA. No differences were observed in maternal perinatal complications. Trial RegistrationClinicalTrials.gov NCT03706872; https://www.clinicaltrials.gov/ct2/show/NCT03706872